The Value of News in the Websites of Regional News Agencies Regarding Iraqi Affairs - Mohsin, Bareq Ali; Abdulrazzaq, Noah Ezzulddin (ALBAHITH ALALAMI, 2023)
This study examines the news values employed by regional news agencies in the selection and dissemination of news concerning Iraqi affairs. Content analysis was conducted on a purposive sample of 596 news articles sourced from official websites of news agencies, including Iraqi, Turkish, and Iranian agencies. The research aims to identify the underlying criteria used by these agencies in determining news suitability for publication.